NILAI MORAL DALAM ANIMASI ADIT DAN SOPO JARWO EPISODE “KEMAH DEPAN RUMAH BIKIN MERIAH” - Lukman Hakim; Moh In’ami (Pascasarjana IAIN Sorong, 2026)
This study aims to investigate how the animated series Adit & Sopo Jarwo contributes to strengthening moral values among Indonesian children. The background of this research actually stems from the researcher’s concern about the reality of moral decline occurring among children in Indonesia. Entertainment media that children in Indonesia watch on a daily basis has become a point of concern, to examine whether its content contains positive values or on the contrary negative ones. One of the entertainment media favored by Indonesian children is animation. One of the animations that is interesting to study is Adit & Sopo Jarwo. This animation is an original Indonesian production that is packaged and presented in accordance whit the culture and traditional values of Indonesian society. This research aims to explore and examine the moral values presented in tha Adit & Sopo Jarwo animation, specifically in the episode “Kemah Depan Rumah Bikin Meriah” and analyze the relevance of this content tho character education for elementary-aged children. Using a qualitative approach and literature study or content analysis, the researcher found at least two types of moral values presented in the Adit & Sopo Jarwo episode “Kemah Depan Rumah Bikin Meriah”